Effect of pre-strain on the strength of similar aluminium EN AW5754-H22 alloy joined by clinching - Shukurea Rahmato Abdulhakim; Zoltán Kovács Péter (MATEC Web of Conferences)
Clinching is a mechanical joining method used to join sheets through plastic deformation. It is widely used in the automotive, aerospace, and home appliance industries due to its cost-effectiveness and ease of integration. The strength of clinched joints is influenced by factors such as die and punch geometry, process parameters, and the pre-strain of sheets. This study investigates the effect of pre-straining on the tensile strength of 5754-H22 aluminium alloy sheets joined by clinching. Pre-strains of 2%, 4%, 6%, and 8% were imposed on each sheet before joining using clinching. Due to pre-strain the thickness of the sheet is reduced. As a result, a reduction in the forming force was recorded in similar pre-strain aluminium alloy sheets joined by clinching. The results showed that as the pre-strain increased, the tensile strength of the clinched joint decreased and a reduction of the elongation was observed. Applying an 8% pre-strain reduced the tensile shear load by approximately 35%. The neck thickness decreased as the pre-strain increased. This study indicates that pre-strain significantly affects the process parameters and quality of clinched joints. To obtain good and resilient clinched joint integrity, the pre-strain should be controlled before the sheet is joined by clinching